Modified maxillomandibular advancement for Eastern Asian patients with moderate or severe OSA: an anatomic and aerodynamic assessment of the upper airway - Li, Kan; Zhao, Tianyu; Liu, Yukun; Cao, Yang; Li, Xiang; Gao, Siyong; Sun, Wei; Wang, Tao; Zeng, Lingchan; Feng, Zhicai; Zheng, Guangsen (Frontiers in Oral Health, 2025)
Background/purposeMaxillomandibular advancement (MMA) is widely used for treating obstructive sleep apnea (OSA) patients. However, conventional MMA may not be suitable for Eastern Asian patients with moderate or severe OSA, as it can lead to unsatisfactory postoperative facial appearance. Hence, modified MMA was reported. Our study aims to evaluate the therapeutic effects of modified MMA on OSA and patient satisfaction with facial appearance. In addition, anatomic and aerodynamic changes in the upper airway were explored.Materials and methodsThis retrospective study included 13 patients with moderate or severe OSA. Overnight polysomnography and the Epworth Sleepiness Scale (ESS) scores were recorded before operation and 6 months after operation to evaluate therapeutic outcomes. Spiral CT scans were performed for all patients to reconstruct 3D configurations of the bony structures and the upper airway. Computational fluid dynamics was performed to analyze aerodynamic characteristics. In addition, correlations between bone segment movements and improvement in airway parameters were examined.ResultsModified MMA achieved successful therapeutic and esthetic outcomes in all cases. The apnea–hypopnea index (36.05 ± 17.68 vs. 5.72 ± 4.76, p < 0.001) and the ESS (13.23 ± 8.9 vs. 6.23 ± 6.81 events/h, p < 0.05) decreased significantly, while the lowest oxygen saturation (76.54 ± 10.26% vs. 84.77 ± 6.02%, p < 0.05) improved greatly. Modified MMA significantly increased the total volume (6,716.55 ± 1,357.73 vs. 11,191.28 ± 2,563.79 mm3, p < 0.001) and the averaged cross-sectional area (117.38 ± 24.25 vs. 201.58 ± 35.76 mm2, p < 0.001) of the upper airway. After modified MMA, the pressure drop, gas velocity, and resistance in the upper airway were all significantly decreased (p < 0.05). Among all the maxillary and mandible sections, the strongest correlation was observed between the advanced movement of the anterior mandible segment and anatomical characteristics of the upper airway.ConclusionModified MMA is an excellent therapeutic method for Eastern Asian patients with skeletal class Ⅱ dentomaxillofacial deformity suffering from moderate to severe OSA; it achieves a balance between esthetic improvement and therapeutic efficacy for OSA both anatomically and aerodynamically.